Appréciation des conditions d’entreposage du riz (Oryza sativa sp) avant le décorticage. Recherche réalisée dans la commune Makiso de la ville de Kisangani, en RDC ; du mois d’Aout 2018 en Septembre 2018. - Julien, NLANDU THUBI; KOMBE LIBENGE Pascal; ABAYA BITIKA Jacques; MUTOBA Hortense; DHECHUVI N’SUNGU Prosper; MBUSE UWEKA Ruphin; NDJANGO (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
For reason of the strong demand of rice on the market consecutive to the galloping demography in the city of Kisangani, a titled research,: "Appreciation of the conditions of rice storage (Oryza sativa sp) has been achieved. The goal of this research is to appreciate the conditions of rice storage (paddy) before the shelling and to drag the possessors riziers to improve the conditions of storage in order to succeed to a growth of technological output of rice to the shelling. The objectives have been set below for this research to know: Identified the rizeries through the common Makiso and the place of paddy source stored; Esteem the rate of paddy humidity stored as well as the middle length of storage; Visited facilities to identify the types of materials of construction of warehouses there; Visited facilities to identify the existing attacks, their size as well as their origin there; Recueillir of various information on the fashion of storage done. To the term of this survey, the gotten results revealed what follows: - The activity of rizerie in the common Makiso is exercised a lot more by men; seen the size of work; - The received paddy is generally dry but his/her/its deterioration is caused by bugs, the rats and the humidity during the length of the storage; - The majority of the possessors riziers is not on the subject professional; reason for which their facilities are constructed with inadequate materials and by ricochet, don’t procure good conditions of storage susceptible to improve the output of rice to the shelling. From where the necessity of sensitization and conscientisation of these last on the norms of storage.